Snipping around for food: Economic, ethical and policy implications of CRISPR/Cas genome editing. Issue 96 (November 2018) - Bartkowski, Bartosz; Theesfeld, Insa; Pirscher, Frauke; Timaeus, Johannes
Abstract: CRISPR/Cas genome editing has the potential to revolutionise agricultural biotechnology and breeding. Also, it can contribute to advancing modern agriculture in multiple respects and lead to shifts in market structure. However, genetic engineering is a highly contested and controversial societal issue. Thus, CRISPR/Cas poses new questions regarding preferences of consumers and producers, food ethics and governance. Precision, easiness-to-use and low costs of CRISPR/Cas make it a viable alternative to conventional breeding. Yet, nature-identical GMOs blur the boundary between nature and technology and result in non-traceability of modifications, which calls for a rethinking of regulatory approaches. Finally, the speed with which the technology advances contrasts with the pace of related societal debates and regulatory processes.